Food advertising on pay-TV for children in Brazil - Cordeiro, Leiliane de Carvalho; Sousa, Alder Mourão de; Paiva, Janaína Braga de; Sá, Naíza Nayla Bandeira de (O Mundo da Saúde, 2023)
Resolution No. 163/2014 deals with the abusiveness of advertisements in general aimed at children. Considering the relevance of the topic for public health, it is important to carry out research on the subject. The objective was to investigate the adequacy of food advertising to Resolution No. 163/2014 in advertisements broadcast by pay-TV channels in Brazil, aimed at children. This is a cross-sectional, quantitative, and descriptive study. Simultaneously, the programming of two pay-TV channels with the highest audience, aimed at children in Brazil, was recorded for 03 complete consecutive days. A structured questionnaire was used to systematize the data. The food/products shown in advertisements were classified into seven groups: sweets, drinks, cereals, restaurant/pizzeria, fast food, dairy products, and snacks. Six types of marketing appeal were identified in the advertisements analyzed: nutritional, affective, gustatory, auditory, visual, and promotional. Principal Component Analysis was performed. More than 50% of the recording hours were used to broadcast advertisements with food content for children. Stimulating emotions and affectivity was the main appeal used to publicize the products. Promises of nutritional benefits, offers of gifts and promotions, and auditory, visual, olfactory, and gustatory stimuli were verified. It is concluded that food advertising does not comply with the norms established by the Resolution and goes against the recommendations that characterize adequate eating habits.